Exploring the Use of Integrating Quora Social Media and Canva: A Sequential Explanatory Study in Secondary School - Dewi Sukmawati; Yuliati; Rahayu Puji Haryanti (Metathesis: Journal of English Language, Literature, and Teaching, 2025)
The integration of ICT has positive effects on current education in secondary schools, especially in teaching Analytical Exposition text writing by using Quora social media and Canva applications. The objectives of this study were to examine students' Analytical Exposition text writing performance and to determine the students’ perceptions of the integration of the applications. A survey questionnaire was collected to gain in-depth information about the integration of applications. By using a sequential explanatory mixed-methods design, the data were collected both quantitative and qualitative. The sample was 36 students of eleventh graders of social programs which was divided into the experimental and control groups. The data collection included giving a pretest and a posttest, followed by a survey questionnaire. The findings indicated that participants in the experimental group achieved a statistically significantly higher score in the writing posttest (70), p < .000 compared to the control group. The questionnaire were obtained applying the Unified Theory of Acceptance and Use of Technology (UTAUT) to assess students’ views on technology use: performance expectations, effort expectations, social influences, and facilitating conditions. The results revealed that the integration applications have positively effects on performance expectations, efforts expectations, social influences and facilitating conditions. The facilitating condition was the highest influence (74.3%) on the students’ perceptions of the learning writing performance, followed by social influence (61.12%), effort expectations (60.19%) and performance expectation (58.33%). The applications facilitated the students’ critical thinking, constructing the ideas and creativity in the writing performance. Furthermore, it also made the students more creative and interactive in the classroom.